SEMA Number 3 of 2023 and Divorce Regulation in Sidoarjo Court: Nomor SEMA 3 Tahun 2023 dan Peraturan Perceraian di Pengadilan Sidoarjo - Taqi, Shofi Mauline Athaliah; Phahlevy, Rifqi Ridlo (Indonesian Journal of Islamic Studies, 2025)
General Background: Divorce rates in Indonesia have shown a consistent increase, prompting the Supreme Court to issue various regulations aimed at maintaining marital harmony. Specific Background: One of these efforts is Supreme Court Circular Letter (SEMA) No. 3 of 2023, which introduces a six-month separation requirement before divorce can be granted in Religious Courts. Knowledge Gap: Despite its legal intent, limited empirical evidence exists on how this regulation affects divorce dynamics at the local court level. Aims: This study investigates the implementation of SEMA No. 3 of 2023 and its practical role in reducing divorce cases at the Sidoarjo Religious Court. Results: Findings reveal that while the policy initially reduced divorce numbers in 2023, the effect was temporary, with cases increasing again in subsequent years due to its non-binding nature. Novelty: The research offers a contextual empirical analysis of SEMA’s role within Indonesia’s Islamic judicial system. Implications: Strengthening the juridical framework and integrating social counseling mechanisms are crucial for ensuring the sustainability of family law reforms in Islamic courts.Highlights: SEMA functions as an internal legal guideline, not binding law. Its temporary effect underscores the need for legal reinforcement. Integration with counseling programs can enhance long-term outcomes. Keywords: SEMA No. 3 of 2023, Divorce, Religious Court, Legal Policy, Islamic Law